2013
DOI: 10.1097/tp.0b013e318278301b
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Expanding the UK Pool of Potential Intestinal Transplant Donors

Abstract: An increased awareness of bowel donation is needed to improve the low offering rate of bowels from DBD donors. A more robust UK bowel allocation system and a formalized European-wide intestinal donor organ sharing program should lead to an increased utilization of available donor bowels and a lower waiting list mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Therefore, the pool of donors who can provide a suitable size‐matched intestinal or multivisceral graft is very small as the median (IQR) weight of pediatric donors in the United Kingdom is 46 (14–62) kg 13 . This is further demonstrated by Rushton et al, who reported only 4 potential small intestine donors were <20 kg over a two‐year period in the United Kingdom 9 . During the same time period, there were up to 10 children on the national waitlist for an intestine‐containing graft 6 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, the pool of donors who can provide a suitable size‐matched intestinal or multivisceral graft is very small as the median (IQR) weight of pediatric donors in the United Kingdom is 46 (14–62) kg 13 . This is further demonstrated by Rushton et al, who reported only 4 potential small intestine donors were <20 kg over a two‐year period in the United Kingdom 9 . During the same time period, there were up to 10 children on the national waitlist for an intestine‐containing graft 6 .…”
Section: Introductionmentioning
confidence: 81%
“…A higher susceptibility of intestinal failure‐associated liver disease (IFALD) in children has necessitated more than 50% of intestinal grafts to be transplanted in conjunction with the liver 5–8 . Obtaining an adequate size‐matched intestine containing graft for small children is challenging, and many may miss their therapeutic window of opportunity for transplantation because of clinical deterioration during a prolonged wait 9,10 . Age and size‐matched pediatric donors are extremely rare in the United Kingdom and Europe in general.…”
Section: Introductionmentioning
confidence: 99%
“…When these children are considered for transplant surgery, it is anticipated that there would be significant disproportion of abdominal volume to donor organs even if size‐matched donors are used. In the United Kingdom, there is a shortage of size‐matched donors, and hence, although organ reduction techniques are used, the recipient abdominal cavity of infants is often too small to accommodate the transplanted organs, as has been reported . These children have a higher risk of mortality on the waiting list, and hence, alternative options have to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are echoed by Rushton et al. , who investigated intestinal utilization rates in the UK, in the year 2011–2012. Forty‐seven percent of non‐utilization by pediatric centers was due to donor size.…”
mentioning
confidence: 88%
“…Over the past two decades, advances in organ preservation, surgical transplantation techniques, immunosuppressive strategies and postoperative management have brought small bowel transplantation from an experimental technique to the preferred treatment option for intestinal failure [1,2]. Treatment success has led to an increased demand for intestinal donors whilst the number of suitable grafts remained static; therefore, researchers have been trying to seek new sources of donors to alleviate this pressure [3].…”
mentioning
confidence: 99%